PENGARUH INDEPENDENSI, KEAHLIAN PROFESIONAL, DAN PENGALAMAN KERJA PENGAWAS INTERN TERHADAP EFEKTIVITAS PENERAPAN STRUKTUR PENGENDALIAN INTERN PADA BANK PERKREDITAN RAKYAT DI KABUPATEN BADUNG - DESYANTI, NI PUTU EKA; DWI RATNADI, NI MADE (Jurnal Ilmiah Akuntansi dan Bisnis, 2008)
Internal controller is crucial in developing effective internal control structure of Bank Perkreditan Rakyat. Because of the important role of internal controller, s/he must be independent, has sufficient professional competencies and working experiences. This study aims to investigate the effect of significant independency, professional competency, and working experience of internal controller simultaneously and partially on the effectiveness of implementation of internal control structure of Bank Perkreditan Rakyat in Badung Regency. Variables used in this study include internal control structure as the dependent variable; and independency, professional competency, and working experience of internal controller as the independent variables. The result shows that independency, professional competency, and working experience of internal controller simultaneously and partially affect the effectiveness of implementation of internal control structure of Bank Perkreditan Rakyat in Badung Regency significantly. And, the most dominant factor is professional competency.
Keywords: independency, professional competency, working experience, internal controller, internal control structure.